Differences between Midvastus and Subvastus TKA Surgical Approaches in the Tasks of Sitting and Standing - Jarvis, Sarah L.; Onstot, Brian R.; Bhowmik-Stoker, Manoshi; Jacofsky, Marc C.; Jacofsky, David J. (The Journal of Knee Surgery, 2013)
The mini-midvastus (MV) approach to total knee arthroplasty (TKA) minimizes damage to the extensor mechanism; however, the mini-subvastus (SV) approach is designed to avoid such damage. Quadriceps weakness following TKA can have a significant impact on the activities of daily living, particularly stand-to-sit down (STSD) and sit-to-stand up (STSU) activities. Fifty-three subjects diagnosed with primary osteoarthritis and scheduled to undergo TKA were randomized to receive an MV or SV surgical approach and were given identical postoperative orders. Compared with age-matched controls, the SV group had a quicker return of normal peak knee extension moment during STSU, whereas the MV group had a quicker return of normal movement patterns in hip, knee, and ankle parameters during STSD yet represented the higher functioning subjects as more MV subjects had difficulty completing the task as instructed. Considering both movements are required for daily living, neither surgical group was found to have a significant advantage over the other in functional outcome through 6 months post-TKA.
Keywords: total knee arthroplasty; sit-to-stand; midvastus; subvastus; quadriceps weakness